Characterizing MOOC Pedagogies: Exploring Tools and Methods for Learning Designers and Researchers - Quintana, Rebecca Mary; Tan, Yuanru (Online Learning, 2019)
We explore new tools and methods for learning designers and researchers to characterize pedagogical approaches that are applied to the design of MOOCs. This paper makes three main contributions to literature on MOOC design and evaluation: (1) an Expanded Assessing MOOC Pedagogies instrument for use by learning designers and researchers within their own contexts, (2) a demonstration of how nearest neighbor cluster analysis can be used to identify pedagogically similar MOOCs, and (3) a preliminary analysis of the clusters to account for features and factors that contribute to pedagogical similarity of MOOCs within clusters. This work advances research in the development of MOOC typologies, to allow learning designers and researchers to ask nuanced questions about pedagogical aspects of MOOC design.